Treatment of Lysosomal Storage Diseases: Recent Patents and Future Strategies - Ortolano, Saida; Vieitez, Irene; Navarro, Carmen; Spuch, Carlos (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2014)
Lysosomal storage diseases (LSDs) are a group of rare genetic multisystemic disorders, resulting in deficient lysosomal activity. These pathologies are characterized by progressive accumulation of storage material within the lysosomes, ultimately leading to organ dysfunctions. LSDs patient’s clinical outcomes have significantly improved, since the advent of enzyme replacement therapy (ERT). ERT is approved worldwide for 6 LSDs: Gaucher disease, Fabry disease, Mucopolysaccharidosis types I, II, and VI, and Pompe disease. The efficacy and safety of ERT for LSDs has been confirmed by extensive clinical trials, however therapy with infused protein is life-long and disease progression is still observed in treated patients. Obstacles to successful ERT, such as immune reactions against the infused enzyme, miss-targeting of recombinant enzymes, and difficult delivery to crucial tissues (i.e. brain and bone), determine the need for further research, in order to ameliorate therapeutic strategies. Viral gene therapy, stem cell based therapy, pharmacological chaperones and could be considered essential tools for future improvement of recombinant enzyme trafficking and targeting. This review will discuss recent patents and new strategic approaches for enzyme delivery to highlight the most relevant aspects, concerning next generation LSDs treatment.
Keywords: Fabry disease